Differentiation between athlete's heart and dilated cardiomyopathy in athletic individuals. Issue 14 (27th April 2020) - Millar, Lynne Martina; Fanton, Zephryn; Finocchiaro, Gherardo; Sanchez-Fernandez, Gabriel; Dhutia, Harshil; Malhotra, Aneil; Merghani, Ahmed; Papadakis, Michael; Behr, Elijah R; Bunce, Nick; Oxborough, David; Reed, Matthew; et al.
Abstract : Objective: Distinguishing early dilated cardiomyopathy (DCM) from physiological left ventricular (LV) dilatation with LV ejection fraction <55% in athletes (grey zone) is challenging. We evaluated the role of a cascade of investigations to differentiate these two entities. Methods: Thirty-five asymptomatic active males with DCM, 25 male athletes in the 'grey zone' and 24 male athletes with normal LV ejection fraction underwent N-terminal pro-brain natriuretic peptide (NT-proBNP) measurement, ECG and exercise echocardiography. Grey-zone athletes and patients with DCM underwent cardiovascular magnetic resonance (CMR) and Holter monitoring. Results: Larger LV cavity dimensions and lower LV ejection fraction were the only differences between grey-zone and control athletes. None of the grey-zone athletes had abnormal NT-proBNP, increased ectopic burden/complex arrhythmias or pathological late gadolinium enhancement on CMR. These features were also absent in 71%, 71% and 50% of patients with DCM, respectively. 95% of grey-zone athletes and 60% of patients with DCM had normal ECG. During exercise echocardiography, 96% grey-zone athletes increased LV ejection fraction by >11% from baseline to peak exercise compared with 23% of patients with DCM (p<0.0001). Peak LV ejection fraction was >63% in 92% grey-zone athletes compared with 17% patients with DCM (p<0.0001). Failure to increase LV ejection fraction >11% from baseline to peak exercise or achieve a peak LV ejection fraction >63% had sensitivity of 77% and 83%, respectively, and specificity of 96% and 92%, respectively, for predicting DCM. Conclusion: Comprehensive assessment using a cascade of routine investigations revealed that exercise stress echocardiography has the greatest discriminatory value in differentiating between grey-zone athletes and asymptomatic patients with DCM. Our findings require validation in larger studies.